Fatty Infiltration Is a Prognostic Marker of Muscle Function After Rotator Cuff Tear. Issue 9 (July 2018) - Valencia, Ana P.; Lai, Jim K.; Iyer, Shama R.; Mistretta, Katherine L.; Spangenburg, Espen E.; Davis, Derik L.; Lovering, Richard M.; Gilotra, Mohit N.
Background: Massive rotator cuff tears (RCTs) begin as primary tendon injuries and cause a myriad of changes in the muscle, including atrophy, fatty infiltration (FI), and fibrosis. However, it is unclear which changes are most closely associated with muscle function. Purpose: To determine if FI of the supraspinatus muscle after acute RCT relates to short-term changes in muscle function. Study Design: Controlled laboratory study. Methods: Unilateral RCTs were induced in female rabbits via tenotomy of the supraspinatus and infraspinatus. Maximal isometric force and rate of fatigue were measured in the supraspinatus in vivo at 6 and 12 weeks after tenotomy. Computed tomography scanning was performed, followed by histologic analysis of myofiber size, FI, and fibrosis. Results: Tenotomy resulted in supraspinatus weakness, reduced myofiber size, FI, and fibrosis, but no differences were evident between 6 and 12 weeks after tenotomy except for increased collagen content at 12 weeks. FI was a predictor of supraspinatus weakness and was strongly correlated to force, even after accounting for muscle cross-sectional area. While muscle atrophy accounted for the loss in force in tenotomized muscles with minimal FI, it did not account for the greater loss in force in tenotomized muscles with the most FI. Collagen content was not strongly correlated with maximal isometric force, even when normalized to muscle size. Conclusion: After RCT, muscle atrophy results in the loss of contractile force from the supraspinatus, but exacerbated weakness is observed with increased FI. Therefore, the level of FI can help predict contractile function of torn rotator cuff muscles. Clinical Relevance: Markers to predict contractile function of RCTs will help determine the appropriate treatment to improve functional recovery after RCTs.